RESPON PERTUMBUHAN TANAMAN KANGKUNG (IPOMOEA REPTANS POIR) TERHADAP PEMBERIAN HARA MIKRO MELALUI AKAR DAN DAUN - Alpandari, Heny; Prakoso, Tangguh (Fakultas Pertanian Universitas Ratu Samban, 2024)
Water spinach is a type of horticultural plant that has high economic value. Water spinach needs nutrients that are quickly available to support its growth. Micronutrients are an important support for plants. There are two ways of providing micronutrients to plants, through roots and through leaves. The aim of this research was to determine the effect of providing complete microfertilizer through the roots and leaves on the growth of kale plants. This research was carried out in June-August 2023, using a single factor Completely Randomized Design (CRD). The treatments consisted of 3, namely control, micro fertilizer given through the roots (watered), micro fertilizer given through the leaves (spray). The observation parameters are: plant height, number of leaves, greenness of the leaves, fresh weight of the crown, fresh weight of the roots, dry weight of the crown, dry weight of the roots, ratio of root shoots, ratio of leaf area and typical leaf weight. The results of the research, providing micronutrients to kale plants through the leaves has a better influence on the parameters of plant height, number of leaves, greenness of the leaves, leaf area and leaf area ratio.